α-Dystroglycan Functions in Acetylcholine Receptor Aggregation But Is Not a Coreceptor for Agrin-MuSK Signaling - Jacobson, Christian (J Neurosci, 1998)
α-dystroglycan (α-DG) is an agrin-binding protein that has been implicated in acetylcholine receptor (AChR) clustering, but it is unclear whether it acts as a coreceptor involved in initial agrin signaling or as a component involved in later events. To investigate its role, we have generated antisense derivatives of the C2 mouse muscle cell line, which have reduced α-DG expression. When compared with wild-type cells, the α-DG-deficient myotubes have a dramatic reduction in the number of spontaneous and agrin-induced AChR clusters. Several findings suggest that this decrease in AChR clustering is likely not because of a defect in agrin signaling through the MuSK receptor tyrosine kinase. Compared with wild-type cells, the α-DG-deficient cell lines showed only a transient reduction in the level of agrin-induced MuSK tyrosine phosphorylation and no reduction in AChR β-subunit tyrosine phosphorylation. Additionally, agrin-induced phosphorylation of MuSK in wild-type myotubes was not decreased using agrin fragments that lack the domain primarily responsible for binding to α-DG. Finally, neural agrin-induced phosphorylation of MuSK was unaffected by treatments such as excess muscle agrin or anti-α-DG antibodies, both of which block agrin–α-DG binding. Together, these results suggest that α-DG is not required for agrin-MuSK signaling but rather that it may play a role elsewhere in the clustering pathway, such as in the downstream consolidation or maintenance of AChR clusters.